A Cambrian mixed carbonate–siliciclastic platform in SW Gondwana: evidence from the Western Sierras Pampeanas (Argentina) and implications for the early Paleozoic paleogeography of the proto-Andean margin - Ramacciotti, Carlos D. (2018)
The Western Sierras Pampeanas (WSP) of Argentina record a protracted geological history from the Mesoproterozoic assembly of the Rodinia supercontinent to the early Paleozoic tectonic evolution of SW Gondwana. Two well-known orogenies took place at the proto-Andean margin of Gondwana in the Cambrian and the Ordovician, i.e., the Pampean (545–520 Ma) and Famatinian (490–440 Ma) orogenies, respectively. Between them, an extensive continental platform was developed, where mixed carbonate–siliciclastic sedimentation occurred. This platform was later involved in the Famatinian orogeny when it underwent penetrative deformation and metamorphism. The platform apparently extended from Patagonia to northwestern Argentina and the Eastern Sierras Pampeanas, and has probable equivalents in SW Africa, Peru, and Bolivia. The WSP record the outer (deepest) part of the platform, where carbonates were deposited in addition to siliciclastic sediments. Detrital zircon U–Pb SHRIMP ages from clastic metasedimentary successions and Sr-isotope compositions of marbles from the WSP suggest depositional ages between ca. 525 and 490 Ma. The detrital zircon age patterns further suggest that clastic sedimentation took place in two stages. The first was sourced mainly from re-working of the underlying Neoproterozoic metasedimentary rocks and the uplifted core of the early Cambrian Pampean orogen, without input from the Paleoproterozoic Rio de la Plata craton. Sediments of the second stage resulted from the erosion of the still emerged Pampean belt and the Neoproterozoic Brasiliano orogen in the NE with some contribution from the Rio de la Plata craton. An important conclusion is that the WSP basement was already part of SW Gondwana in the early Cambrian, and not part of the exotic Precordillera/Cuyania terrane, as was previously thought.